Heat tranfer phenomena in falling liquid films: A synergistic experimental and computational study - Charogiannis,A; Denner,F; Van,Wachem BGM; Kalliadasis,S; Markides,CN (2018)
We employ planar laser-induced fluorescence (PLIF), particle tracking velocimetry (PTV) and infrared thermography (IR) towards the detailed investigation of the flow and heat transfer phenomena underlying harmonically-excited, gravity-driven film flows falling over an inclined, electrically-heated substrate. PLIF is used to generate space and time-resolved film-height measurements, PTV to retrieve two-dimensional (2-D) velocity-field information, and IR to recover the temperature of the film free-surface. The experiments are complemented by direct numerical simulations (DNSs) that provide additional information on the liquid temperature, viscosity and velocity distributions between the flow inlet and the location along the axial direction of the flow where optical measurements are conducted. By adoption of this synergistic approach, we recover results on the spatiotemporal evolution of the flow and temperature fields, and link the variation of the gas-liquid interface temperature along the waves to the variation of the local film-height, flow-rate and streamwise and cross-stream velocity components. Despite the intermittent observation of localized hotspots in the experiments, which constitute precursors to the formation of thermal rivulets, the mean wall-temperature, bulk liquid-temperature and gas-liquid interface temperature display clear trends with respect to the mean film-thickness, which largely dictates the heat transfer performance of the examined film flows.